Zoonotic emerging infectious disease in selected countries in Southeast Asia: Insights from ecohealth - Grace, Delia; Gilbert, Jeffrey; Lapar, Ma. Lucila; Unger, Fred; Fèvre, Eric M.; Hung Nguyen-Viet; Schelling, E. (Springer, 2011)
Most emerging diseases of humans originate in animals, and zoonotic emerging infectious diseases (EIDs) threaten human, animal, and environment health. We report on a scoping study to assess actors, linkages, priorities, and needs related to management of these diseases from the perspective of key stakeholders in three countries in Southeast Asia. A comprehensive interview guide was developed and in-depth interviews completed with 21 key stakeholders in Vietnam, Lao People’s Democratic Republic, and Cambodia. We found numerous relevant actors with a predominance of public sector and medical disciplines. More capacity weaknesses than strengths were reported, with risk analysis and research skills most lacking. Social network analysis of information flows showed policy-makers were regarded as mainly information recipients, research institutes as more information providers, and universities as both. Veterinary and livestock disciplines emerged as an important “boundary-spanning” organization with linkages to both human health and rural development. Avian influenza was regarded as the most important zoonotic EID, perhaps reflecting the priority-setting influence of actors outside the region. Stakeholders reported a high awareness of the ecological and socioeconomic drivers of disease emergence and a demand for disease prioritization, epidemiological skills, and economic and qualitative studies. Evaluated from an ecohealth perspective, human health is weakly integrated with socioeconomics, linkages to policy are stronger than to communities, participation occurs mainly at lower levels, and equity considerations are not fully considered. However, stakeholders have awareness of ecological and social determinants of health, and a basis exists on which transdisciplinarity, equity, and participation can be strengthened.